Answer:
- A
Step-by-step explanation:
9x-4/x=3 ok first lets get the like terms together! So 9x+1x=10x rewrite 10x-4=3 add 4 to both sides 10x=7 then divide 10 7/10=.7 x=.7
Or you can do it this way
9x-4/x=3 combine like terms so times -4 to both sides 3*-4=-12 rewrite 9x+x=-12 combine like term (still got some) 9x+1x=10x rewrite 10x=-12 divide 10 to both sides -12/10=-1.2 rewrite x=-1.2 (I'm like 95% sure it's this one) hope this helps!!! Have a nice nite (Don't be afraid to ask me about details on this or another question)!!!
We apply the Pythagorean theorem twice and obtain:
12 ^ 2 = x ^ 2 + (15-d) ^ 2
9 ^ 2 = x ^ 2 + d ^ 2
We observe that it is a system of two equations with two unknowns whose solutions are:
(x, d) = (-36/5, 27/5)
(x, d) = (36/5, 27/5)
We ignore the negative solution, therefore, the solution is:
(x, d) = (36/5, 27/5)
Answer:
The length of the new fence is:
x = 36/5 meters
Answer:
just typed the whole in mathaway.com
Step-by-step explanation:
it's a better app for quadratic equation and you can use it on a school computer
Answer:
The third one is right.
Step-by-step explanation: